Multiple-System Atrophy with Cerebellar Predominance Presenting as Respiratory Insufficiency and Vocal Cords Paralysis - Ramon Andrade Bezerra de Mello; Diana Ferreira; José Manuel Dias da Costa; Maria José Rosas; João Manuel Quinaz (Case Reports in Medicine)
Background. MSA (Multiple System Atrophy) may be associated either with Parkinsonism or with cerebellar ataxia (MSA-c subtype). It is considered a rare disease, but many patients are misdiagnosed as suffering from idiopathic Parkinson's disease. In this paper, we report a case of a patient admitted with respiratory failure and vocal cords paralysis due to MSA-c. Case Report. A 79-year-old Caucasian woman was admitted in March 2010 with dyspnea, asthenia, stridor, and respiratory failure needing noninvasive ventilation. She had orthostatic blood pressure decline, constipation, insomnia, daytime sleepiness, and snoring. The neurologic examination revealed cerebellar ataxia. A laryngoscopy revealed vocal cord paralysis in midline position and tracheostomy was performed. The Brain Magnetic Resonance Imaging revealed atrophy of middle cerebellar peduncles and pons with the “hot cross bun sign.” Conclusion. Although Multiple-system atrophy is a rare disease, unexplained respiratory failure, bilateral vocal cord paralysis, or stridor should lead to consider MSA as diagnosis.